Digitalisasi Pendidikan Poltekimipas: Tantangan Performa Jaringan dalam Mendukung Pembelajaran Modern (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2026)
Educational digitalization has become a strategic step in improving the quality of learning in the modern era. The utilization of digital technologies such as Learning Management Systems (LMS), video conferencing, and online-based administrative systems requires educational institutions to have optimal network infrastructure. Politeknik Imigrasi dan Pemasyarakatan (Poltekimipas), as an official higher education institution, has also implemented digital-based learning systems to enhance the effectiveness and efficiency of the teaching and learning process. However, the implementation of educational digitalization still faces various challenges, particularly related to network performance in supporting modern learning activities. This study aims to analyze the challenges of network performance in supporting educational digitalization at Poltekimipas and to identify solutions that can be implemented to improve network service quality. The research method used is a qualitative descriptive method with a literature study and observation approach toward network usage within the educational environment. The results show that the main challenges include limited bandwidth, unstable internet connections, high network latency, and the increasing number of simultaneous network users. These conditions affect the effectiveness of online learning and access to digital educational services. Therefore, the development of network infrastructure, increased bandwidth capacity, and optimization of network management are necessary to support the success of educational digitalization at Poltekimipas.